2013
DOI: 10.5296/jpag.v3i3.6224
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Antecedents of Job Satisfaction and further its impact on Organizational Commitment

Abstract: The Human capital plays a vital role in success of any organization. The contended and committed employee is a key to achieve organizational objective. There are several researches conducted to understand the function of worker's satisfaction and commitment towards job but this area of study is remain unexposed. The purpose of this study is to discuss and examine the forces which lead to private and govt sector workers Job satisfaction and organizational commitment. A theoretical model was anticipated and test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Quantitative and descriptive research methods were used in the study Employee views regarding the benefits of training and development and three components of organizational commitment (affective, normative, and continuance) are the focus of this study. A thorough literature review indicated that most of research in the context of training and commitment used a quantitative approach (Chambel & Sobral, 2011;Javeria, 2013;Khan & Iqbal, 2020b).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Quantitative and descriptive research methods were used in the study Employee views regarding the benefits of training and development and three components of organizational commitment (affective, normative, and continuance) are the focus of this study. A thorough literature review indicated that most of research in the context of training and commitment used a quantitative approach (Chambel & Sobral, 2011;Javeria, 2013;Khan & Iqbal, 2020b).…”
Section: Methodsmentioning
confidence: 99%
“…Affective commitment allows people to work with dedication, accept the goals and objectives of their employers, and contribute to the organization's success (Hashmi, Ahmad, & Nawaz, 2021;Ullah, Kamran, Akram, Nawaz, & Rehman, 2021). An affective commitment should result in a higher level of happiness at work, a higher level of commitment and less turnover (Javeria, 2013;Khan & Iqbal, 2020b). When an individual considers the perceived cost of time, money, and effort invested in the organization before leaving, it develops into a continuous commitment.…”
Section: Literature Review 21 Training and Organizational Commitment (Affective Normative And Continuance)mentioning
confidence: 99%
See 1 more Smart Citation
“…Environmental performance is quantified using a Paille et al, (2014). Organizational commitment through Allen et al (1996) and job satisfaction is measured through the scale used by Javeria et al (2013). Respondents were presented with a set of environmental performance indicators and questioned about their company's potential to meet them.…”
Section: Methodsmentioning
confidence: 99%
“…Mail and survey data were used to compile this information. Committed and satisfied employees are more likely to work towards achieving organizational objective that leads to the greater performance of organization (Javeria et al, 2013;Junaid, Bashir, Nasim, & Ahmad, 2021;…”
Section: Satisfaction and Loyalty Of Customersmentioning
confidence: 99%